Áfricas Transatlânticas e dimensões patrimoniais: diálogos com Stefania Capone (Tempo e Argumento, 2025)
In the first half of November 2023, anthropologist and CNRS researcher Stefania Capone was in Florianópolis for some academic activities, including the lecture “Between Oyó and Ilê-Ifé: the impact of Yoruba history on the reconfigurations of the heritage field in the South Atlantic (Nigeria/Brazil)”, which she gave at the Santa Catarina State University (UDESC) on November 9. This was the opportunity for the interview presented here, which took place in the same week, at UDESC's Public History and Cultural Heritage Laboratory.
Keywords: History of Africa; Cultural Heritage; Religiosity; Candomble; Nigeria History; Transnational